Cloning and characterization of Bombyx mandarina prophenoloxidase gene PPO1 - ZHANG Yong-liang; SHENG Dong-feng; ZHU Yong (浙江大学学报. 农业与生命科学版, 2012)
The complemental deoxyribonucleic acid (cDNA) of Bombyx mandarina prophenoloxidase gene PPO1 was cloned by reverse transcription-polymerase chain reaction (RT-PCR). The results showed that the cDNA with 2 086 bp in length contained an open reading frame (ORF) of 2 058 bp which encoded 685 amino acid residues. The deduced amino acid sequence had a high identity to the reported sequence of PPO1 from other lepidopterous insects and shared the typical structural features of PPO from other insects. The PPO1 gene was only expressed in head and blood of B. mandarina by RT-PCR, and only expressed in blood by Northern blot analysis. These results provide a molecular basis for further studying the function of PPO1 gene in B. mandarina.